Drivers of biodiversity loss in freshwater environments: A bibliometric analysis of the recent literature - Williams‐Subiza, Emilio A.; Epele, Luis B. (Aquatic conservation, 2021)
Species are disappearing at a rate comparable with previous mass extinctions. Freshwater environments are being particularly affected, with biodiversity losses occurring much faster in freshwater than in terrestrial or marine ecosystems. This study assessed the research on drivers of biodiversity loss in freshwater environments as described in nearly 37,000 articles published in the last decade. Articles on biodiversity published between 2010 and 2019 were retrieved from the Web of Science to determine the number of articles that addressed a particular driver of biodiversity loss, by analysing the titles, s, and keywords. The biodiversity and development status of a country was also investigated to see how it affects its scientific output (i.e. number of published articles). Twenty per cent of the articles on biodiversity addressed freshwater biodiversity. Researchers devoted considerable effort to six drivers – climate change, water pollution, flow modification, expanding hydropower, species invasions, and habitat degradation – but practically ignored other threats, such as plastic and light pollution. It was also found that megadiverse countries, which for the most part were also developing countries, published substantially fewer articles than developed but less biodiverse countries. We recommend a series of actions that could contribute to mitigate the biases found in this study.